Reduksi Resiko dan Peningkatan Efisiensi Kerja Kelompok Nelayan Sampan Layar di Desa Alasrejo Kecamatan Wongsorejo Kabupaten Banyuwangi - Rubiono, Gatut; Martaviano, Bayu Septa (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2020)
Fishermen in the coastal area of Kebunrejo hamlet, Alasrejo village, Wongsorejo sub district, Banyuwangi district are traditional fishermen. The boat used is a small boat with a sail. Catching fish is carried out by fishing line which is stretched out with strings. Storage of catches using simple foam boxes. The use of sail has weather problems that cause the total fishing trip travel time to be Â± 5 hours. The amount of travel time and a simple storage box causes the freshness of the fish to be not optimal and the selling value is relatively low. Community partnership program activities are carried out with the aim of increasing the income level of fishermen with the application of diesel engines with propellers. The partners are 4 (four) fishermen. Activities carried out by designing, manufacturing and using a 24 Hp diesel engine with 2 blades brass propeller as a replacement for the sail driving power. The results of the activity show that the partners get technical benefits including improvements to boat propulsion device, increased speed of movement of boats at sea, relatively low fuel needs and operating costs, and income opportunities from actors in sea fishing tourism.